The Boron Efflux Transporter ROTTEN EAR Is Required for Maize Inflorescence Development and Fertility . Issue 7 (17th July 2014) - Chatterjee, Mithu; Tabi, Zara; Galli, Mary; Malcomber, Simon; Buck, Amy; Muszynski, Michael; Gallavotti, Andrea
Abstract : This work reports the isolation and characterization of a mutant called rotten ear ( rte ), which shows growth and fertility defects in maize inflorescences. rte is required for the uptake and transport of the micronutrient boron and is necessary for the structural integrity of maize cell walls. Abstract: Although boron has a relatively low natural abundance, it is an essential plant micronutrient. Boron deficiencies cause major crop losses in several areas of the world, affecting reproduction and yield in diverse plant species. Despite the importance of boron in crop productivity, surprisingly little is known about its effects on developing reproductive organs. We isolated a maize ( Zea mays ) mutant, called rotten ear ( rte ), that shows distinct defects in vegetative and reproductive development, eventually causing widespread sterility in its inflorescences, the tassel and the ear. Positional cloning revealed that rte encodes a membrane-localized boron efflux transporter, co-orthologous to the Arabidopsis thaliana BOR1 protein. Depending on the availability of boron in the soil, rte plants show a wide range of phenotypic defects that can be fully rescued by supplementing the soil with exogenous boric acid, indicating that rte is crucial for boron transport into aerial tissues. rte is expressed in cells surrounding the xylem in both vegetative and reproductive tissues and is required for meristem activity and organ development. We show that low boron supply to the inflorescences results in widespread defects in cell and cell wall integrity, highlighting the structural importance of boron in the formation of fully fertile reproductive organs.